2016
DOI: 10.1111/1477-9552.12153
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Practices and the Growth of US Cash Rent Leases

Abstract: Over the past 20 years the ratio of cash rent to cropshare land leases across the US has more than doubled. We test different theories that might explain this, and conclude that the shift is mostly the result of revolutionary changes in cultivation practices. The switch from conventional to conservation tillage brought about by changes in herbicide technologies, genetically modified seeds, increased fuel costs, and knowledge of the benefits of soil micro‐organisms, has reduced a tenant‐farmer's ability to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This suggests that the biophysical benefits associated with NT and cover crops might take a long period of continuous use before they can realize any economic advantage, which is consistent with the conclusion of Soule, Tegene, and Wiebe (). Findings by Allen and Borchers () also confirmed that yield variability or production risk may be reduced by practicing NT.…”
Section: Restults and Discussionmentioning
confidence: 72%
“…This suggests that the biophysical benefits associated with NT and cover crops might take a long period of continuous use before they can realize any economic advantage, which is consistent with the conclusion of Soule, Tegene, and Wiebe (). Findings by Allen and Borchers () also confirmed that yield variability or production risk may be reduced by practicing NT.…”
Section: Restults and Discussionmentioning
confidence: 72%
“…However, developed countries have private and government insurance programs and futures and options markets that reduce production and price risk, lowering the need for risk‐sharing contracts. Allen and Lueck (1992b,1993, 1998, 1999) and Allen and Borchers (2016) argue that in the United States, transaction costs and not risk preferences are the primary driver of contract choice. Huffman and Fukunaga (2008) and Fukunaga and Huffman (2009) find evidence more supportive of risk‐sharing using data from the 1999 Agricultural Economics and Land Ownership Survey.…”
Section: Rental Contract Risk and Incentives And Sharecroppingmentioning
confidence: 99%
“…If the burden of property tax is fully passed from a landowner to a renter, then its effects may deter production or change the riskiness of the planting decisions for the renter. As an example of the relationship between production practices and cash rents, Allen and Borchers (2016) find that the increased prevalence of cash rent contracts, as opposed to crop share rental contracts, has been the result of no‐till cultivation practices that have reduced the ability of a renter to exploit the landowner's soil. However, if none of the tax is passed on to the renter and is fully paid by the landowner, then taxing agricultural land would be decoupled from the farming decisions of the operators.…”
mentioning
confidence: 99%